2014
DOI: 10.1016/j.scitotenv.2014.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Human and bovine viruses in the Milwaukee River watershed: Hydrologically relevant representation and relations with environmental variables

Abstract: To examine the occurrence, hydrologic variability, and seasonal variability of human and bovine viruses in surface water, three stream locations were monitored in the Milwaukee River watershed in Wisconsin, USA, from February 2007 through June 2008. Monitoring sites included an urban subwatershed, a rural subwatershed, and the Milwaukee River at the mouth. To collect samples that characterize variability throughout changing hydrologic periods, a process control system was developed for unattended, large-volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 64 publications
8
60
5
Order By: Relevance
“…In this study, the data also showed the occurrence of HAdV in samples of river water present in all points and with a mean frequency of 54 % (39 to 83 %) along the SRB. These data corroborate other studies that found detection rates ranging from 29 to 96 % in surface waters in South Korea, Germany, Brazil, and USA (Lee et al 2005;Jurzik et al 2010;Rigotto et al 2010;Fongaro et al 2012;Miagostovich et al 2014;Corsi et al 2014). Point 1 had the highest rate HAdV detection (83 %); This point is characterized by having the lowest population density.…”
Section: Adenovirus Detectionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the data also showed the occurrence of HAdV in samples of river water present in all points and with a mean frequency of 54 % (39 to 83 %) along the SRB. These data corroborate other studies that found detection rates ranging from 29 to 96 % in surface waters in South Korea, Germany, Brazil, and USA (Lee et al 2005;Jurzik et al 2010;Rigotto et al 2010;Fongaro et al 2012;Miagostovich et al 2014;Corsi et al 2014). Point 1 had the highest rate HAdV detection (83 %); This point is characterized by having the lowest population density.…”
Section: Adenovirus Detectionsupporting
confidence: 90%
“…Although this stretch is characterized by an increase in population and presents characteristics of intense disturbance, in a landscape with less rural components than the upper section, it is still possible to detect nonhuman adenovirus species at high concentrations, and the most frequently detected were CAV 51.66 % (1.19×10 6 GC/ l), followed by AvAdV 10.12 % (3,33×10 5 GC/l), BAdV 5.83 % (1.09×10 6 GC/l), and PAdV 4.17 % (9.31×10 5 GC/ l) (Figs. 2 and 3b,c,d,and e), showing that the contamination along the river takes on characteristics of diffuse contamination, because it receives effluent loads dragged through surface runoff coming from various sources along the watercourse Corsi et al 2014;Oliveira and Henkes 2013).…”
Section: Adenovirus Detectionmentioning
confidence: 99%
“…The highest levels of animal virus detection were associated with higher relative water flow conditions and relatively higher daily rainfall, suggesting more spatially uniform hydrologically driven inputs (e.g., surface runoff, tile drainage, and in-stream mobilization of antecedent waters/sediment/stream detritus [55,85]). HEV detection was also linked to relatively higher daily rainfalls, as well as higher relative water electrical conductivity values (i.e., salts).…”
Section: Detection and Densities Of F-specific Coliphage And Viruses mentioning
confidence: 99%
“…Although baseflow separation using the digital filter method is performed by signal processing without physical meaning, the digital filter method has been used in many applications of baseflow separation (e.g., [17,20,31,34,42]) due to its speed, consistency, and reproducibility [17]. Direct runoff and baseflow using the digital filter method can be estimated by Equations (1) and (2).…”
Section: Digital Filter Methodsmentioning
confidence: 99%
“…For this reason, many governments and institutions have installed gauging stations to periodically measure streamflow. Baseflow and direct runoff, which are the main components of streamflow, provide seasonally different contributions to river flow [1,2]. For example, the intensification of direct runoff during the wet season can cause soil erosion and deposition and water pollution (e.g., non-point pollution and suspended sediment).…”
Section: Introductionmentioning
confidence: 99%